探析中印文化碰撞之跨文化交际——以中国赴印尼汉语教师的工作学习生活采访为例 - Paula Aretha (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2024)
With the opening and development of Chinese language education in Indone-sia, the number of people learning Chinese in Indonesia has also increased significantly. That way the demand for Chinese teachers in Indonesia is in-creasing slowly . In 2004, Hanban launched the